Strengthening of reinforced concrete structure using sprayable fiber-reinforced cementitious composites with high ductility - Huang, Bo-Tao; Li, Qing-Hua; Xu, Shi-Lang; Zhou, Bin (Composite structures, 2019)
Fiber-reinforced cementitious composites with high ductility exhibit significant pseudo-strain-hardening response and multi-cracking behavior. In this paper, a systematical investigation of a sprayable fiber-reinforced cementitious material with high ductility is presented from material design to practical application. This sprayable material is formed using the wet-mix spray process, and its compressive, tensile, and flexural strengths are higher than those of the cast ones with the same proportion. A series of reinforced concrete beams, including unloaded and pre-loaded ones, is strengthened with this material, and the four-point bending test is performed to evaluate the flexural performance of the composite elements. A theoretical analysis is conducted to predict the load capacity of the specimens. The application cases of this sprayable material in China are presented to show its potential application in the construction of durable concrete structures and restoration of aged structures.